2009
DOI: 10.1111/j.1365-3180.2009.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of hydrology on the growth and physiology of an invasive exotic, Lygodium microphyllum (Old World climbing fern)

Abstract: Summary We conducted a glasshouse study to examine effects of hydrology on the growth and physiology of Lygodium microphyllum (Old World climbing fern), an invasive exotic that is rapidly colonising forested wetlands in Florida, USA. We assessed the fern’s growth and physiological responses to three hydrological treatments – flood, drought and field capacity. To further explore the physiology of the treatment responses of L. microphyllum, we also sprayed each plant with gibberellic acid, paclobutrazol (gibbere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 42 publications
(61 reference statements)
0
11
0
Order By: Relevance
“…The allometric relationship between stem length and total mass (R 2 = 0.92) from the initial harvest was developed to estimate the initial plant mass of the experimental plants and to calculate the relative growth rate (RGR) (Gandiaga et al 2009). The RGR (mg g -1 day -1 ) was calculated for each individual plant used for the experiment following the method by Evans (1972):…”
Section: Harvest and Plant Nutrient Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The allometric relationship between stem length and total mass (R 2 = 0.92) from the initial harvest was developed to estimate the initial plant mass of the experimental plants and to calculate the relative growth rate (RGR) (Gandiaga et al 2009). The RGR (mg g -1 day -1 ) was calculated for each individual plant used for the experiment following the method by Evans (1972):…”
Section: Harvest and Plant Nutrient Analysismentioning
confidence: 99%
“…It has the ability to grow in varying hydrological (Gandiaga et al 2009), nutrient (Volin et al 2010), and light conditions (Volin et al 2004). Analysis of soil samples from both its native range and invaded region has shown that although L. microphyllum grows in highly acidic soils in its native range in Australia, it is thriving in close-to-neutral soils in Florida (Soti et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Managing L. microphyllum has been a significant challenge for land resource managers and researchers due to its extensive rapid invasion in natural areas of south Florida. Once established, L. microphyllum dominates both understory and overstory native wetland habitats, and has the ability to grow in varying hydrological (Gandiaga et al 2009), nutrient (Volin et al 2010), soil pH (Soti et al 2014, and light gradients (Volin et al 2004). Soti et al (2014) have shown that L. microphyllum is highly dependent on mycorrhizal fungi for growth and phosphorus uptake which could highly enhance its invasiveness.…”
Section: Introductionmentioning
confidence: 99%
“…The rhizome grows at, or just below, the soil surface and, once established, can withstand temporary inundation and variable water levels (Gandiaga et al 2009, Mueller 1982a, Volin et al 2004. Leaves form dorsally on the rhizome, follow a single rank, and develop from a single cell produced by the apical meristem (Mueller 1982a).…”
Section: Fern Biologymentioning
confidence: 99%